Adsorption behavior of the copolymer AM/DMC/APEG/DMAAC-16 on a carbonate rock and its application for acidizing. Issue 50 (21st June 2017) - Quan, Hongping; Chen, Zhonghao; Wu, Yang; Li, Zhuoke
Abstract : The adsorption mechanism and adsorption behavior of a quadripolymer on the carbonate rock was researched. Abstract : In this study, a quadripolymer of acrylamide (AM), [2-(methacryloyloxy)ethyl]-trimethylammonium chloride (DMC), allyl polyethylene glycol (APEG), and hexadecyl trimethyl allylammonium chloride (DMAAC-16) was designed and synthesized, which was named PADAD. The molecular structure of PADAD was characterized by Fourier transform infrared (FT-IR) and nuclear magnetic resonance ( 1 H-NMR) spectroscopy. The molecular weight and the dispersion exponent of PADAD were determined by gel permeation chromatography (GPC). The adsorption behavior of PADAD on a carbonate rock surface was investigated. The kinetic model of PADAD on a carbonate rock surface was found to fit the pseudo-second-order kinetic model. The adsorption isotherm model of PADAD on the surface of a carbonate rock fitted with the Freundlich model. Addition of PADAD into 20% HCl obviously reduced the rate of the acid rock reaction. We analyzed the microstructure of the rock surface by scanning electron microscopy (SEM) and found that an adsorption film appeared on the rock surface due to PADAD, which could reduce the contact of acid with the rock surface.